Regularity Criteria of the Magnetohydrodynamic Equations in a Bounded Domain (Journal of Partial Differential Equations, 2023)
Regularity criteria in terms of bounds for the pressure are derived for the 3DMHD equations in a bounded domain with slip boundary conditions. A list of threeregularity criteria is shown.
Keywords: Magnetohydrodynamic equations; regularity criterion; bounded domain.